2015
DOI: 10.1007/s00330-015-3967-x
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral insufficiency fractures of the femoral head: associated imaging findings and predictors of clinical progression

Abstract: Objectives To characterize the morphology and imaging findings of femoral head subchondral insufficiency fractures (SIF), and to investigate clinical outcomes in relation to imaging findings. Methods Fifty-one patients with hip/pelvis magnetic resonance (MR) images and typical SIF characteristics were identified and reviewed by two radiologists. Thirty-five patients had follow-up documentation allowing assessment of clinical outcome. Subgroup comparisons were performed using regression models adjusted for age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(40 reference statements)
2
17
0
1
Order By: Relevance
“…Thin bone trabeculae indicated the presence of osteoporosis, which is a major risk factor for SIF (Yamamoto and Bullough 1999;Ikemura et al 2013) It is also possible that the present patient might have developed SIF of the right femoral head considering the radiological findings, although there was no histopathological examination. The resolution of symptoms with conservative treatment was consistent with the previously reported cases of SIF (Bangil et al 1996;Rafii et al 1997;Yoon et al 2014;Hackney et al 2016;Sonoda et al 2016). Furthermore, increased uptake in the bilateral femoral heads on bone scintigraphy was also compatible with SIF (Rafii et al 1997;Yamamoto and Bullough 1999;Iwasaki et al 2011), without a "cold in hot" appearance, which is compatible with ON (Sugano et al 1999).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thin bone trabeculae indicated the presence of osteoporosis, which is a major risk factor for SIF (Yamamoto and Bullough 1999;Ikemura et al 2013) It is also possible that the present patient might have developed SIF of the right femoral head considering the radiological findings, although there was no histopathological examination. The resolution of symptoms with conservative treatment was consistent with the previously reported cases of SIF (Bangil et al 1996;Rafii et al 1997;Yoon et al 2014;Hackney et al 2016;Sonoda et al 2016). Furthermore, increased uptake in the bilateral femoral heads on bone scintigraphy was also compatible with SIF (Rafii et al 1997;Yamamoto and Bullough 1999;Iwasaki et al 2011), without a "cold in hot" appearance, which is compatible with ON (Sugano et al 1999).…”
Section: Discussionsupporting
confidence: 89%
“…The prognosis of SIF may depend on the initial treatment, as well as the degree of osteopenia (Yamamoto et al 2008). Restricted weight-bearing can be successful in SIF, and about a half (Yoon et al 2014;Hackney et al 2016) or twothirds (Sonoda et al 2016) of SIF cases might improve without surgical treatment. Precise diagnosis might contribute to a better outcome by avoiding early arthroplasty in young women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that cartilage defect size is associated with a clinical subchondral insufficiency fracture of the femoral head progression. 11 Further investigations with histopathological assessments at both the femoral head and acetabulum are necessary to clarify the impact of comorbid BME lesions on the prognosis of subchondral insufficiency fracture of the hip.…”
Section: Discussionmentioning
confidence: 99%
“…BME, which invariably accompanies this lesion, was reported to be an insignificant predictor of clinical progression. 62 Small cartilaginous defect size, smaller fracture diameter, and parallel morphology with regard to the joint surface were suggested as good prognostic factors. 62 Surrounding muscle edema, synovitis, and hip joint effusion represent additional common features.…”
Section: Imagingmentioning
confidence: 96%